Symetryczny czy niesymetryczny? Problemy w opisie frazeologicznych par aspektowych - Iwona Kosek (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica)
The article focuses on a few problems a researcher may encounter while analysing phraseological units which form aspectual pairs, obtained from text and lexicographical data. In the first as either symmetrical or asymmetrical in their aspect (forming an aspectual pair or not). In the second part, and in the summary, the provided examples and causes of the observed discrepancies are studied in greater detail. It appears that whether a phraseological unit forms an aspectual pair or not is decided by a number of semantic and grammatical factors. The status of particular units is individually decided. For a few such units [e.g., działać na kogoś jak (czerwona) płachta na byka (to make someone extremely angry, lit: to act like a red rag for a bull), kamień na kamieniu nie zostanie z czegoś (not one stone will be left standing, lit: there will be no stone left upon stone)], an emergence of an aspectual counterpart may be treated as an outcome of language evolution (from an imperfective form to both, perfective and imperfective forms). In the case of unclear aspectual symmetry, the status of such units will probably be decided by usage (frequency of use).